Proposta de uma abordagem para a gestão de solicitação de alteração para testes automatizados para o setor de TI de uma corporação - Cristofoli, Lauren Girardi (Universidade do Vale do Rio dos Sinos, 2017)
This paper introduces the results of an action research applied in the information technology sector of an organization, in which a formal automated test change management process was applied. The purpose of this work was to design and evaluate how software configuration management practices can improve the processes of creating and changing automated tests by implementing a formal management cycle for requesting changes in test cases.
Keywords: Tecnologia de informação; Gestão formal; Testes automatizados; Information technology; Formal management; Automated testing